Occupational therapy interventions in the treatment of people with severe mental illness. Issue 4 (July 2017) - Höhl, Werner; Moll, Sandra; Pfeiffer, Andreas
Abstract : Purpose of review: Life expectancy of people with severe mental illness is considerably shortened and their risk for cardiovascular and metabolic disorders is increased. They spend more time in solitary and less time in structured activities than the general population. Engagement in healthy patterns of activity, including active, meaningful participation in the community can, therefore, be critical to recovery from severe mental illness. Occupational therapy is a profession that focuses on time use, activity patterns and occupational engagement, and the links to health and well-being. In this study, we review research evidence regarding approaches to occupational engagement, including behavioural activation, time use, and activity promotion. We also will review studies that specifically evaluate the impact of occupational therapy interventions. Recent findings: There is a growing body of evidence regarding the value of interventions addressing occupational engagement of individuals with severe mental illness, including a range of activation strategies and approaches. There is a need, however, for documentation of theoretically informed approaches that are supported by fidelity measures to ensure standardization. Summary: Larger-scale studies are needed, including consistent outcome measures to document engagement and changes in activity patterns as well as health-related outcomes. High-quality randomized clinical trials are important to establish effectiveness. As occupational therapy interventions are complex and embedded within a range of multidisciplinary approaches, new models of pragmatic trials within the naturalistic context of psychiatric rehabilitation are also needed.